2013
DOI: 10.1186/1936-6434-6-33
|View full text |Cite
|
Sign up to set email alerts
|

Eminent scientists reject the supernatural: a survey of the Fellows of the Royal Society

Abstract: Fellows of the Royal Society of London were invited to participate in a survey of attitudes toward religion. They were asked about their beliefs in a personal God, the existence of a supernatural entity, consciousness surviving death, and whether religion and science occupy non-overlapping magisteria (NOMA). Overwhelmingly the majority of Fellows affirmed strong opposition to the belief in a personal god, to the existence of a supernatural entity and to survival of death. On 'NOMA', the majority of Fellows ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
1
13
1
Order By: Relevance
“…There are few if any studies comparing views of religion and evolution among biologists, chemists, and physicists. Though Stirrat and Cornwell () found that eminent biologists tend to be less religious than physicists, here we found an unpronounced difference in religiosity (Figure ) when comparing physicists and biologists of the same academic degree level. Furthermore, it is interesting that in our study, we found that physicists actually supported slightly more a Darwinian view of the evolutionary process than did biologists (Figure ), although this difference is not significant.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…There are few if any studies comparing views of religion and evolution among biologists, chemists, and physicists. Though Stirrat and Cornwell () found that eminent biologists tend to be less religious than physicists, here we found an unpronounced difference in religiosity (Figure ) when comparing physicists and biologists of the same academic degree level. Furthermore, it is interesting that in our study, we found that physicists actually supported slightly more a Darwinian view of the evolutionary process than did biologists (Figure ), although this difference is not significant.…”
Section: Discussioncontrasting
confidence: 61%
“…University scientists at the UACh are more secular than the rest of Chilean society, which is a pattern also seen in other countries (Leuba ; Leuba and Kantor ; Larson and Witham , ; Gross and Simmons ; Stirrat and Cornwell ). Academic affiliation and experience have an important effect on religious disbelief and acceptance of evolution by academic scientists and science students at the UACh.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Approximately 35% of the public believes that it is not possible to accept God and evolution , and 55% of the public agreed that science and religion are often in conflict (Masci 2009). Interestingly, a recent study of eminent scientists in the Royal Society showed that about equal numbers of scientists agreed and disagreed with the statement that religion and science are non-overlapping domains of discourse and can peacefully coexist, 28.4% vs. 24.3%, respectively; however, biological scientists were more likely to say they see a conflict between science and religion than physical scientists (Stirrat and Cornwell 2013). Elite scientists at both the National Academies of Science (Larson and Witham 1998) and the Fellows of the Royal Society (Stirrat and Cornwell 2013) overwhelmingly reject a belief in God -only about 8% of both groups indicated belief (Lugo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In three other polls in 1981, 2005, and 2006, about a third of respondents thought it was not possible to believe in both God and evolution (Plutzer and Berkman, ). The enormous disparity between the degree of belief in God of elite scientists (about 7% of the US scientists at the National Academy of Sciences and 8% of British Fellows of the Royal Society; Larson and Witham, , Stirrat and Cornwell, ) and the general public (95%: Gallup and Lindsay, ) has been noted as evidence for incompatibility of science and religion (Coyne, ). Yet, a more recent study of nearly 1,700 scientists found that nearly half are religious, and many others label themselves as “spiritual,” with only a small minority of them actively hostile toward religion (Ecklund, ).…”
Section: Poll Datamentioning
confidence: 99%